Konstruksi Budaya Pada Komunitas One Piece Tangerang Selatan - Hervian, Naufal Fadhila; Saputra, Faisal Tomi; Mirza, Mochammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
This thesis examines Japanese culture as popular culture which can be a factor in the construction of identity among fans of Japanese culture within the One Piece community, South Tangerang. This thesis aims to identify how Japanese culture can be one of the triggering factors for someone to use his identity as a fan in his daily life by showing a lifestyle that is different from his environment. This thesis uses qualitative methods with data collection techniques of observation, interviews, and in-depth observations of five informants. The concept used to analyze this thesis is Cultural Identity in the perspective of Cultural studies from Hall Stuart and Cris Barker. In the view of cultural studies, cultural identity explains how individuals construct identities beyond their original identities by using signs and symbols. The conclusion of this thesis is that Japanese fan culture can unknowingly enter and become the dominant culture in an individual when the individual starts consuming it. The representations made by fans are different for each fan. This is due to the difference in interpreting the existing symbols. Like, wearing Japanese-themed clothes, interacting with Japanese, using attributes (key chains or pins), and even drawing manga characters. because cultural identity has a dynamic nature that makes cultural identity diverse and developing. An example is a fan who continued to draw manga and eventually he was able to make his own Anime series, which gave rise to a Cultural Imperialism